The impact of macroeconomic risk factors, the adoption of financial derivatives on working capital management, and firm performance - Reyad, Hossain Mohammad; Zariyawati, Mohd Ashhari; Ong, Tze San; Muhamad, Haslinah (Multidisciplinary Digital Publishing Institute, 2022)
This study examines macroeconomic risk factors to investigate how they affect working capital management (WCM) and, ultimately, firm performance. Additionally, we examine the effect of credit default swaps (CDSs) as a countermeasure for WCM in the presence of volatile macroeconomic risk factors. In doing so, we use firm-level data from the United States, the United Kingdom, Germany, and China between 2006 and 2020. The two-step system generalized method of moments (GMM) estimation method is employed to analyze the study′s objectives. Results show that US, German, and Chinese firms are more conservative, while UK firms are more aggressive in maintaining WCM during economic policy uncertainty. Conversely, foreign exchange risks drive the USA, the UK, and Chinese firms to lengthen their cash conversion cycle level due to fear of value loss, while the opposite is true for German firms. Nevertheless, following CDS adoption, firms are more confident in working capital (WC) investment. CDSs eliminate the need for delayed receivables and payables and increased inventory as safety stock for US, UK, and Chinese firms. Finally, CDS interaction shows that USA, UK, and German firms may boost their profitability by increasing account receivable periods to create more sales, reducing account payable periods, and holding more inventories to expedite sales operations. Alternatively, CDSs suggest an optimal level of WC investment for Chinese firms. As a result, governments should consider CDS adoption in policy decisions when business performance sinks due to macroeconomic volatility.